Hiệu quả và năng suất tổng hợp của khu vực Đông Nam Bộ, Việt Nam giai đoạn 2010 – 2021 - Hồ Quốc, Thông (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study analyzes the efficiency and productivity of the Southeastern provinces in Vietnam during the period from 2010 to 2021. This paper utilizes data from the provincial statistical yearbooks and employs the Färe-Primont technique to measure total factor productivity (TFP), efficiency, and decomposition of the components of TFP. The key results indicate a decline in the growth momentum of both TFP and economic growth in the Southeastern provinces from 2016 to 2021. This study highlights the substantial variations in growth, productivity, efficiency, and quality of growth across the provinces. There is considerable potential for improving resource use efficiency, which could increase the gross regional domestic product (GRDP) of the entire region by around 10%, equivalent to VND 180 trillion per year. The results also demonstrate the negative impact of the global pandemic and other issues on economic growth, as well as total factor productivity and resource use efficiency. Therefore, the solution to improving the quality of resources, which is closely linked to the efficiency of capital use, is expected to contribute to enhancing overall productivity growth.